Infectious Complications of Intrathecal Drug Administration Systems for Spasticity and Chronic Pain: 145 Patients From a Tertiary Care Center. Issue 5 (12th January 2015) - Malheiro, Luis; Gomes, Armanda; Barbosa, Paula; Santos, Lurdes; Sarmento, Antonio
<x xml:space="preserve">Abstract</x> Objectives Studies on the use of intrathecal perfusion devices (IPD) are still limited and therefore the aim of this study is to access the infectious complications associated to these devices. Materials and Methods A retrospective analysis of 145 patients who had an IPD implanted at the Chronic Pain Unit of Hospital de São João over the last 20 years. Mean follow‐up time was 7.24 years (range: 0.47–17.41 years). Intrathecal antispastic drug perfusion was used in 123 patients (84.8%) and intrathecal analgesia in 22 patients. Results A total of 19 (8.71%) infections involving the IPD were identified of which, 14 (6.4%) were surgical site infections (SSIs). Methicillin‐sensitive Staphylococcus aureus was the most commonly isolated bacteria in this group. Superficial SSIs were treated with oral antibiotic treatment or local wound care, while in deep SSI the pump was removed. Meningitis was identified in 5 (2.3%) patients and was always preceded by deep surgical site infections, some of which were already being treated with intravenous antibiotics. Median time to meningitis development was 2.2 months (IQR 82.58 months), after the introduction of the pump. Pump removal with anti‐biotherapy were the treatment of choice. One patient died of a septic shock with associated meningitis and urinary tract infection. Conclusions As seen in this study, infectious complications following implantation of IPD are not uncommon and include a variety of microorganisms. Antibiotic therapy without pump removal may be enough for superficial surgical site infections, but our data suggests that pump removal is the treatment of choice for deep infections as the infection may proceed to meningitis.